Evolutionary and depositional geological model of the Regência paleocanyon in the onshore region of the Espírito Santo Basin (Cretaceous-Eocene) - Batiston, Denis Antonio [UNESP]; Rohn, Rosemarie [UNESP]; Vincentelli, Maria Gabriela Castillo [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
The Regência paleocanyon, recognized in the subsurface of the Espírito Santo Basin, was carved from the Cretaceous and filled up until the middle Eocene. Data from 31 seismic sections, 29 wells, and biostratigraphic markers have substantiated the conception of geological models that enhance knowledge about the evolution and morphology of the paleocanyon. The results include stratigraphic correlations, structural geology interpretations, and stratigraphic surfaces determination (tops of the Mariricu, São Mateus, Regência, and Urucutuca formations), morphologic contour maps and schematic sections. Since its beginning, the Regência paleocanyon was related to faults in the basement. A first, long shallow channel is evidenced near the top of the Aptian Mariricu Formation. The paleocanyon is divided into proximal and distal blocks by an N-S system of normal faults designated as Cedro-Rio Doce Fault Zone (ZCCRD). The morphology of the paleocanyon was also controlled by smaller normal faults with SW-NE direction. These faults originated in the basement and were active until the almost complete fill of the paleocanyon. Normal faults were also determinant in the carving of a secondary large channel in the southwestern region, as well as other smaller channels along the northern margin. In the proximal region, late Cretaceous deposits may have been preserved due to its downward movement and rotation along normal faults. It can be inferred that, during the Eocene, both the proximal region and the paleocanyon depocenter were infilled by sediments from the same source. Seismic reflectors evidence the occurrence of abundant, stacked cut-and-fill channels in the lower part of the paleocanyon and upslope gradation to scattered channels. The set of interpretations is schematically synthesized through an evolutionary and depositional geological model.
Modelo geológico evolutivo e deposicional do paleocânion de Regência, região onshore da Bacia do Espírito Santo, Cretáceo ao Eoceno
Keywords: Cretaceous; Drift phase; Eocene; Marginal basin; Urucutuca Formation